Spesies of Plants used for Natural Care Beauty by Gayo Womens in Bener Meriah - Ernilasari; Saudah (Universitas Serambi Mekkah, 2024)
The utilization of plants as traditional cosmetics has been used by Gayo women in Bener Meriah Regency for generations. The use aims to maintain natural beauty to minimize the use of chemicals that often cause many side effects. Information related to the species of plants used has not been recorded properly, so it is feared that the information will be degraded over time. This study aims to find out about the species of plants used as natural beauty care ingredients by Gayo women in Bener Meriah. This research used an exploratory survey method. Sampling was conducted by snaw ball sampling. Samples included housewives from the Gayo tribe, teenagers, and people who use plants as hair care. Data were analyzed descriptively qualitatively and data were displayed in the form of tables and figures. The results showed that there are 45 species of plants used in the beauty care of Gayo women spread in diverse families. Rutaceae and Poaceae are the families with the most species, totaling 6 species.